Ellagic Acid Attenuates BLM-Induced Pulmonary Fibrosis via Inhibiting Wnt Signaling Pathway - Li, Xiaohe; Huang, Kai; Liu, Xiaowei; Ruan, Hao; Ma, Ling; Liang, Jingjing; Cui, Yunyao; Wang, Yanhua; Wu, Shuyang; Li, Hailong; Wei, Yuli; Li, Zeping; et al. (Frontiers in Pharmacology, 2021)
Idiopathic pulmonary fibrosis is a progressive lung disease with high mortality and limited therapy that is characterized by epithelial cell damage and fibroblast activation. Ellagic acid is a natural polyphenol compound widely found in fruits and nuts that has multiple pharmacological activities. In this study, we explored the potential effects and mechanisms of Ellagic acid on pulmonary fibrosis in vivo and in vitro. In vivo studies showed that Ellagic acid significantly alleviated bleomycin (BLM)-induced pulmonary fibrosis in mice. In vitro experiments indicated that Ellagic acid could suppress Wnt signaling and attenuate Wnt3a-induced myofibroblast activation and the phosphorylation of Erk2 and Akt. Further studies showed that Ellagic acid could induce autophagy formation in myofibroblasts mainly by suppressing mTOR signaling and promoting apoptosis of myofibroblasts. In vivo experiments revealed that Ellagic acid significantly inhibited myofibroblast activation and promoted autophagy formation. Taken together, our results show that Ellagic acid effectively attenuates BLM-induced pulmonary fibrosis in mice by suppressing myofibroblast activation and promoting autophagy and apoptosis of myofibroblasts by inhibiting the Wnt signaling pathway.